The Importance of Fit: Predictive Power of Work Values on Turnover Intention in the Shanghai Banking Industry - Duan, Jingyan; Yu, Shun-Chi (Rajapark Journal, 2025)
This study examines how work values influence turnover intention through the mediating effects of person-organization fit and person-vocation fit in Shanghai's banking sector. Analysis of 633 questionnaires from diverse banking institutions revealed that (1) work values positively correlate with both person-organization fit and person-vocation fit, (2) both fits significantly reduce turnover intention, and (3) work values exert both direct negative effects and indirect effects through dual mediating pathways on turnover intention. Notably, these relationships remain consistent across state-owned and non-state-owned banks, suggesting evolving employee priorities in China's changing economic landscape. The findings provide theoretical foundations for recruitment strategies and employee development while potentially reducing turnover-related costs for both employers and employees.